Pengaruh Kualitas Kinerja Karyawan Terhadap Pelayanan Tamu Hotel Swissbel Harbour Bay Batam - Gultom, Bastian Kevin; Situmorang, Steven Slamat Obed; Silalahi, Vito Andrian Immanuel (Tourism, Hospitality And Culture Insights Journal, 2025)
This study aims to determine the effect of employee performance quality on the level of service received by hotel guests. In the hospitality industry, employees have a central role in creating a positive guest experience. Employee performance includes various aspects such as work skills, attitudes, responsibilities, speed, and interpersonal communication skills. This study uses a quantitative approach with a survey method on guests and management of starred hotels in the Harbour Bay Batam area. The results of the analysis show that there is a significant and positive relationship between employee performance quality and service satisfaction felt by guests. Employees who have high performance are proven to be able to provide more responsive, friendly, and professional services. Therefore, improving employee competence and motivation is very important in supporting the overall quality of hotel services. This study recommends ongoing training programs and performance-based reward systems as strategies for improving the quality of hotel services.